Shaping the Future of PR Education: Creating a Digital Public Relations Textbook for Course - Nelly Armayanti; Dodi Pramana; Alfi Nura (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teaching Public Relations courses is essential for the Office Administration study program at the Faculty of Economics, Medan State University (FE UNIMED). Current learning materials are outdated and lack alignment with the industrial revolution 4.0, potentially resulting in suboptimal knowledge for future organizational leaders. Thus, updating teaching materials is crucial to ensure students receive contemporary and sharp knowledge in the digital context. This study aims to compile and develop textbooks for Public Relations courses within a digital context, using the ADDIE development model. The ADDIE model includes five stages: Analysis, Design, Development, Implementation, and Evaluation. This Research and Development (RnD) approach ensures a comprehensive development process, enhancing the relevance and effectiveness of the course material. In the Analysis stage, current course materials and student needs were assessed to identify gaps. The Design phase involved structuring the content to incorporate digital public relations concepts. During Development, the textbook was created, integrating modern communication strategies and digital tools. The Implementation stage involved testing the textbook in classroom settings. Evaluation included assessing the textbook's Validity, Effectiveness, and Practicality. The newly developed textbooks provided a contemporary framework for understanding public relations in the digital era. Validation results showed high relevance and accuracy, while effectiveness tests indicated improved student engagement and comprehension. Practicality assessments confirmed ease of use for both students and lecturers. These outcomes highlight the importance of regularly updating educational materials to align with technological advancements and industry needs. Updating Public Relations teaching materials to reflect digital advancements is vital for preparing students as future organizational leaders. The ADDIE model proved effective in developing relevant and practical textbooks. Future research should focus on long-term impacts of these updated materials on student performance and career readiness.